Sintesis Alkil N-asetilglukosamina (Alkil-GlcNAc) dengan Enzim N-asetilheksosaminidase yang diisolasi dari Aspergillus sp. 501 - Saskiawan, Iwan; Handayani, Rini (Perhimpunan Biologi Indonesia, 2011)
ABSTRACTEnzymatic Synthesis of Alkyl N-acetylglucosamine (Alkyl-GlcNAc) by Application ofTransglycosylation Activity of ?-N-Acetylhexosaminidase from Aspergillus sp. 501. ?-NAcetylhexosaminidasefrom Aspergillus sp. 501 has transglycosylation and hydrolytic activity.Transglycosylation occur through transfer of N-acetylglucosamine (GlcNAc) which washydrolyzed from p-nitrophenyl-?-N-acetylglucosamine (pNP-GlcNAc) to various alcohols. Thetransglycosylation product was determined by Thin Layer Chromatography and HighPerformance Liquid Chromatography. Using this transglycosylation activity the novelcompound of Alkyl-GlcNAc was synthesized using N-acetylchitotriose as a donor and anethanol as an acceptor.Keywords: Alkyl N-acetylglucosamine, Transglycosylation, ?-N-Acetylhexosaminidase,Aspergillus sp. 501